Mediamania? Contemporary German Poetry in the Age of New Information Technologies: Thomas Kling and Durs Grünbein - Erk Grimm (Studies in 20th & 21st Century Literature, 1997)
The essay examines the preoccupation with information technologies as a dominant theme of German poetry in the 1980s and 1990s. Outlining the historical shift from a critique of mass media to the ironic affirmation of hi-tech media, the investigation seeks an understanding of its driving forces. The analysis of Enzensberger's polemical essays on the culture industry shows the parallels and the difference in attitude between him and younger poets of the 1980s. A concise account of their publications illuminates the development of an aesthetically demanding poetry that kept aloof from the mass media. In their rejection of a common quotidian or sentimental tone, poets such as Thomas Kling and Durs Grunbein created new idioms and challenging forms while concentrating on hi-tech media as an epochal phenomenon. The sober reflection and technical terminology originate in a materialistic attitude, driven by the desire to regain the power of sophisticated aesthetic expression and to compensate for the loss of experience caused by the simulation of the past.The essay closes with a critical interpretation of the "mediamania" of the 1990s by giving heed to the fashionable remixing of poetic idioms that leaves the false impression of a new school of media poets.
Keywords: information technologies; German poetry; theme; dominant; 1980s; 1990s; critique of mass media; mass media; hi-tech media; ironic; driving forces; understanding; Enzensberger; polemical essays; culture industry; poets; poetic; publication; quotidian; sentimental tone; Thomas Kling; Durs Grunbein; new idioms; idioms; forms; form; epochal phenomenon; materialistic attitude; desire; sophisticated aesthetic; mediamania; critical; new school of media poets